Digital Marketing Tiktok: Bagaimana Meningkatkan Keputusan Pembelian pada Produk Skincare - Anggi, Septiani; Humairoh (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
TikTok launched the TikTok Shop feature to make it easier for consumers to shop without switching applications. This study aims to determine the effect of online customer rating, influencer marketing, and brand trust on purchasing decisions for The Originote Skincare at TikTok Shop. This study uses a quantitative approach with the population, namely Generation Z in Tangerang Regency. The sampling technique used is non probability sampling with a purposive sampling approach. The sample used amounted to 100 respondents. The data analysis tool used is SPSS version 28. The results of this study indicate that partially, the online customer rating variable and the brand trust variable have a positive and significant effect on purchasing decisions. In contrast, the influencer marketing variable has a negative and significant effect on purchasing decisions. Simultaneously online customer rating, influencer marketing, and brand trust have a positive and significant effect on purchasing decisions. The results of the multiple determination coefficient tests obtained an Adjusted R-Square value of 0,931 or 93,1%, indicating that the online customer rating, influencer marketing, and brand trust variables affect purchasing decisions by 93,1%, and other variables influence the remaining 6,9%, not examined in this study. The novelty of this research is that no research examines together that online customer ratings, influencer marketing, and brand trust are important factors that can shape purchasing decisions. This study provides recommendations for skincare brands to maintain consumer ratings and focus more on selecting relevant influencers to increase brand trust and purchase decisions at TikTok Shop. Keywords: Brand Trust, Influencer Marketing, Online Customer Rating, Purchase Decision